Study on evasion and permanence in vocational technical courses - Rodrigues, Adriege Matias (2022)
This article aims to analyze the causes of permanence and evasion of students of vocational technical courses offered by the Colégio Agrícola Vidal de Negreiros (CAVN), located in the Center of Human, Social and Agrarian Sciences, campus III of the Federal University of Paraíba. The methodology of this study is qualitative based and was based on the semi-structured interview instrument. After the analysis of the data found, we evidenced that the causes of evasion and permanence in the professionalizing technical courses of CAVN consist of: family distance; lack of motivation; not identifying with the course.